2017
DOI: 10.1007/s10067-017-3568-y
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Castleman’s disease associated with IgA vasculitis (Henoch-Schönlein purpura) responding well to tocilizumab: a case report

Abstract: A 41-year-old man was referred to our hospital for the evaluation of hypergammaglobulinemia (IgG 2898 mg/dL and IgA 587 mg/dL), inflammation (CRP 6.7 mg/dL and serum interleukin-6 (IL-6) 15.1 ng/L), and anemia (Hb 10.9 mg/dL). Castleman's disease (CD) was diagnosed by axillary lymph node biopsy. Five months later, painful purpura (multiple palpable 5 mm lesions) developed on his legs, gradually spreading to the upper limbs, thighs, and trunk, accompanied by arthralgia of the wrists, ankles, and knees. Skin bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…IL-6, IL-12, TGF-1ß, and TNF-α are the main cytokines proposed to drive POEMS symptoms (29). Oshima et al (30) suggested that the overproduction of IL-6 may contribute to vasculitis as well as the pathogenesis of CD. Furthermore, increased IL-6 in MCD causes B cell proliferation and VEGF secretion, which is critical to the pathogenesis of haemangiomas (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, IL-12, TGF-1ß, and TNF-α are the main cytokines proposed to drive POEMS symptoms (29). Oshima et al (30) suggested that the overproduction of IL-6 may contribute to vasculitis as well as the pathogenesis of CD. Furthermore, increased IL-6 in MCD causes B cell proliferation and VEGF secretion, which is critical to the pathogenesis of haemangiomas (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, pathological analysis revealed that the major pathological type of UCD and MCD was the hyaline-vascular type and plasma-cell type, respectively. In this study, there were 8 cases of progressive enlargement of lymph nodes (4.0–7.0 cm in diameter), including 2 cases in retroperitoneal lymph nodes, 4 cases in cervical lymph nodes, and 2 cases in mediastinal lymph nodes, suggesting that the risk of enlargement of lymph nodes is higher in CD child patients, showing differences from adults with enlargement of abdominal and mediastinal lymph nodes [ 17 ]. There is a lack of significant lymphatic symptoms in the initial stage of the disease, but local compression can occur with the constant enlargement of lymph nodes, leading to different symptoms based on the different sites of compression.…”
Section: Discussionmentioning
confidence: 99%
“…However, since there is no standard therapy, treatment recommendations for CD can be difficult [ 3 ]. Recently, TCZ was shown to be effective for treatment and has been widely used in Japan since June 2005 [ 1 , 2 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%